Development and Evaluation of Psychometrically Equivalent Trisyllabic Words for Speech Audiometry in Fante - Honu-Mensah, C.M (University Of Ghana, 2015)
Background: Speech is pervasively used for communication purposes but can also be used to measure the hearing of individuals, for hearing aids evaluation and for differential diagnoses of cochlea and retrocochlear disorders. Hence, there is the need for the existence of appropriate speech tests to adequately assess speech and predict the degree of hearing impairment. Aim: The aim of this research was to develop and evaluate digitally recorded speech materials that can be used for speech audiometry in Fante. Methods: A quantitative research approach which employed a three-phase cross-sectional study design was adopted for this study. Purposive sampling technique was used in selecting samples throughout the three phases of this study. Fifty-one (51) familiar trisyllabic words were selected from 107 commonly used trisyllabic Fante words, digitally recorded and edited to yield the same RMS as the 1 kHz calibration tone. Listener evaluation was done by 20 native Fante speakers with normal hearing thresholds. Logistic regression was then used to calculate the slope, intercepts and psychometric function slope at 50%/dB and from 20-80%/dB for all the words. To increase homogeneity of the thresholds of the selected words, the intensity of each was digitally adjusted so that the 50% threshold of each word was equal to the mean PTA of the subjects. Results: A final list of 25 familiar homogenous words having the same tone patterns with slopes greater than 7%/dB were finally selected and recorded unto a CD for speech audiometry in Fante. Conclusion: Psychometrically equivalent trisyllabic words for speech audiometry in Fante were developed and evaluated. The need to develop speech audiometry materials in other spoken languages in Ghana is recommended. Keywords: Speech audiometry, homogeneity, psychometric function, familiarity.
Thesis (MSc)
Keywords: Speech audiometry; homogeneity; psychometric function; familiarity; Ghana